Bone Scaffold Geometrical Design And Material Selection By Using Analytical Hierarchy Process For Additive Manufacturing Process - Maidin, Shajahan; Loo, Heoy Shin; Alkahari, Mohd Rizal; Samat, Khairul Fadzli; Yahaya, Saifudin Hafiz (Penerbit UTM Press, 2015)
Bone scaffold is used to aid the regenerative of human organ tissues that caused by a bone fracture. Bone fracture is normally caused by the exertion of exceeding force to the bone that could not be borne or due to bone disease such as osteoporosis. Hence, the use of bone scaffold is needed to provide comfort to a patient and to slowly replace the metal plate for bone implants. Since there is demand in the market for an effective bone scaffold design, the objective of this research is to study the application of Additive Manufacturing (AM) and bone scaffold design in medical application as well as to compare the effectiveness of several materials for its application. Four design of bone scaffolds had been proposed and simulated for compression test and torsional test. A CAD software was used to design bone geometrical structure. In order to select the best bone scaffold design, Analytical Hierarchy Process (AHP) was used as the method to assist in the selection process. Based on the comparative analysis of different design, it was found that Design 1 was the best design. This was mainly due to its geometrical feature that permits higher strength compared to the other geometrical structure of the design. Furthermore, this research compares three different types of materials, namely Alumina Bio-ceramic, Bio-active Glasses and Calcium Phosphate Bioceramic. The comparative analysis showed that the best material was Alumina Bio-ceramic. This material has the highest strength compared to other materials due to its capability to sustain the force exerted on it and hence fulfil the priority setting of choosing the material with the highest strength as the main criteria. However, this material is the most expensive material compared to other two materials.